Values at Work: The Impact of Personal Values in Organisations. Issue 2 (22nd January 2019) - Arieli, Sharon; Sagiv, Lilach; Roccas, Sonia
Abstract : This paper reviews and integrates past research on personal values in work organisations, seeking to portray the role personal values play in shaping the choices and behaviour of individuals in work settings. We start by addressing the role of values in the occupational choice people make. We then review research on the relationships of personal values to a variety of behaviours at work. We continue with discussing the multiple paths through which managers' values affect organisations and their members. In the last section, we address the interplay between organisational levels, and discuss the congruency between personal and organisational values and its implications for organisations and their employees. Together, the research reviewed indicates how the broadness and stability of values make them an important predictor of behaviour at various levels of the organisation. We end by discussing directions for future research on values in organisations.